Metabolic-associated fatty liver disease as assessed by the Fatty Liver Index among migrant and non-migrant Ghanaian populations - Dijk, Anne-Marieke van; Dingerink, Sjoerd; Chilunga, Felix Patience; Meeks, Karlijn Anna Catharina; Bahendeka, Silver; Schulze, Matthias Bernd; Danquah, Ina; Osei, Tracy Bonsu; Serné, Erik; Agyemang, Charles; Holleboom, Adriaan Georgius (Journal of clinical and translational hepatology, 2021)
Metabolic-associated fatty liver disease (MAFLD) is driven by high caloric intake and sedentary lifestyle. Migration towards high income countries may induce these driving factors; yet, the influence of such on the prevalence of MAFLD is clearly understudied. Here, we investigated the Fatty Liver Index (FLI), a proxy of steatosis in MAFLD, after migration of Ghanaian subjects.